Effects of dexmedetomidine on renal system and on vasopressin plasma levels. Experimental study in dogs - Villela, Nivaldo Ribeiro [UNESP]; Do Nascimento Jr., Paulo [UNESP]; De Carvalho, Lídia Raquel [UNESP]; Teixeira, Andrey [UNESP] (My University, 2005)
BACKGROUND AND OBJECTIVES: Perioperative acute renal failure increases morbidity and mortality. Alpha2-adrenergic agonists used in anesthesia increase urinary output and maintain cardiovascular stability. This study aimed at investigating the effects of dexmedetomidine on renal system and on vasopressin plasma levels in anesthetized dogs. METHODS: This study involved 36 adult mixed-breed dogs anesthetized with propofol, fentanyl, and isoflurane, which were randomly distributed in three groups receiving: G1 -20 mL of 0.9% saline in 10 minutes, followed by 20 mL of the same solution in one hour; G2 -20 mL of 0.9% saline with dexmedetomidine (1 μg.kg-1) in 10 minutes, followed by 20 mL of the same solution with the same dexmedetomidine dose (1 μg.kg-1) in one hour; and G3 -20 mL of 0.9% saline with dexmedetomidine (2 μg.kg-1) in 10 minutes, followed by 20 mL of the same solution with the same dexmedetomidine dose (2 μg.kg-1) in one hour. Renal and hemodynamic variables and vasopressin plasma levels were studied in four periods: M1 (control) - immediately after the stabilization period; M2 - after initial injection of the solution being studied, coinciding with the beginning of continuous injection of the same solution; M3 - 30 minutes after M2; and M4 - 30 minutes after M3. RESULTS: Dexmedetomidine has decreased heart rate and maintained adequate cardiovascular stability, as cardiac output was kept constant. Urinary output was increased for G2 and G3 as compared to G1. For G2 and G3, urinary osmolality has decreased in M3 and M4. For G3, values of free water clearance were increased throughout the experiment. Vasopressin plasma levels have decreased for G3, resulting in lower values as compared to G1 and G2 in M2 and M4. CONCLUSIONS: In anesthetized dogs, low doses of dexmedetomidine inhibit vasopressin secretion, causing aqueous diuresis. These actions might protect kidneys during ischemic events. © Sociedade Brasileira de Anestesiologia, 2005.
Efeitos da dexmedetomidina sobre o sistema renal e sobre a concentração plasmática do hormônio antidiurético. Estudo experimental em cães
Keywords: Animals: dogs; Renal system: vasopressin